The Implementation of Regulation About Enhanced Recovery After Caesarean Surgery in Indonesia: A Literature Review - Iswahyudi, Iswahyudi; Kartika, I Gusti Ayu Putri; Purwani, Sagung Putri ME; Manuaba, Ida Bagus Gede Fajar (Postgraduate, University of Mataram, 2023)
Enhanced Recovery After Cesarean Surgery (ERACS) has been popular since the COVID-19 pandemic to reduce the length of stay in the hospital which is risky for spreading the virus. Apart from that, ERACS is also aimed at reducing the level of pain and accelerating the ability to mobilize. This study aimed to review journal articles related to the implementation of ERACS in Indonesia based on the Decree of The Minister of Health of The Republic of Indonesia Number Hk.01.07/Menkes/1541/2022 Concerning National Guidelines for Medical Services for Anesthesiology and Intensive Therapy related to medical, ethical, and legal trends and initiative ERACS to the concept of pain management as a human right. This study used Scholar Google as a search database using keywords: (